DAMPAK SUBSIDI RASKIN TERHADAP ASUPAN GIZI RUMAHTANGGA MISKIN DI INDONESIA - Lili Theresanti Muslimah; Prani Sastiono (FEB Universitas Sultan Ageng Tirtayasa, 2019)
In this study we estimate the impact of the Raskin subsidy policy on poor households' nutritional intake in Indonesia. The effect of Raskin subsidies on household rice consumption, calories from eight household consumption commodities and total household calories usingdemand function theory. Households are grouped according to the amount of rice consumption before the Raskin subsidy policy was implemented. The hypothesis of Raskin subsidy impact on calorie consumption is positive. Using panel data approach and two-stage regression (2SLS) is estimated coefficient, whether there is substitution effect or income effect. Suspected of endogenous relationship between rice consumption and subsidy then used the interaction ownership of social protection card and Post as an instrument variable. The results of the study showed that the impact of subsidies on calories is increasing in household groups with low rice consumption level, while the high level of calories consumption is reduced.